2008
DOI: 10.1063/1.2840721
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of enhanced magnetic anisotropy in FeCo alloys

Abstract: The structural, electronic, and magnetic properties of FeCo alloys were studied by first-principles calculations. It has been found that the alloys prefer chemically noncubic geometries in a wide composition range. This produces appreciable uniaxial magnetic anisotropy, which facilitates interphase magnetic interaction and enhances the overall magnetization in exchange-coupled nanocomposite systems. Large magnetostrictive coefficients provide another venue for manipulations of magnetic anisotropy energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The presence of a finite coercive field and a higher remanent magnetisations in FeCo alloy nanoparticles compared to Co nanoparticles of the same size (and deposited under the same conditions onto identical substrates) is unexpected. FeCo alloys are usually soft magnetic materials with very high saturation magnetisation fields and very low coercive fields 47. Thus, the respective magnetic anisotropy energies should be very small, at least much smaller than those of Co.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a finite coercive field and a higher remanent magnetisations in FeCo alloy nanoparticles compared to Co nanoparticles of the same size (and deposited under the same conditions onto identical substrates) is unexpected. FeCo alloys are usually soft magnetic materials with very high saturation magnetisation fields and very low coercive fields 47. Thus, the respective magnetic anisotropy energies should be very small, at least much smaller than those of Co.…”
Section: Resultsmentioning
confidence: 99%
“…Note that Wu et al . have shown that the binding energy/cell (−0.51 eV/cell) is minimum for (FeCo) 8 cluster when it is in bcc configuration30. Following the thermal spike temperatures raised in respective fluences, we have performed ab initio molecular dynamics (MD) simulations under the frame work of DFT to first understand the structural changes of the bcc (FeCo) 8 cluster at those temperatures (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, for FeCo monolayers epitaxially grown on MgO (001), the in-plane lattice is enlarged to match that of MgO(001) ( a = 2.97 Å), while the out-of-plane lattice is shortened to 2.71 Å, leading to a c / a ratio of 0.91. It has been reported that the MAE reduces as the c / a ratio decreases and becomes negative when it is smaller than 1 for B2-FeCo alloy [ 28 ]. Hence, a negative MAE is anticipated in Fe 8 Co 8 /MgO.…”
Section: Resultsmentioning
confidence: 99%